Competitive Advantage as a Catalyst Aligning Entrepreneurial and Market Orientations in Sumbawa MSMEs - Hardiansyah, Rian; Mikhratunnisa (JURNAL ECONOMINA, 2026)
This research examines the influence of market orientation (MO) and entrepreneurial orientation (EO) on the performance of micro, small, and medium enterprises (MSMEs), with particular emphasis on the mediating effect of competitive advantage (CA). Anchored in the principles of the Resource-Based View and Dynamic Capabilities Theory, the study argues that strategic orientations can only enhance firm outcomes once they are effectively transformed into durable competitive strengths.A quantitative causal approach was employed through a structured survey administered to MSME managers and business owners in Sumbawa Regency. Data were processed using Partial Least Squares Structural Equation Modeling (SEM–PLS). The analysis demonstrates that EO exerts a significant direct effect on MSME performance, whereas MO contributes indirectly via CA. Both strategic orientations show positive associations with competitive advantage, which subsequently leads to improved performance outcomes. The model demonstrates strong explanatory and predictive capability, reflected in R² values of 0.591 for CA and 0.706 for performance, supported by substantial Q² values. Overall, the results suggest that MO and EO generate meaningful performance improvements only when strategically leveraged to build sustainable competitive advantage. The study enriches theoretical discourse on MSME strategic behavior and offers practical insights to strengthen innovation capacity, responsiveness, and adaptability.